2021
DOI: 10.1038/s41467-021-22070-x
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetically regulated digital signaling defines epithelial innate immunity at the tissue level

Abstract: To prevent damage to the host or its commensal microbiota, epithelial tissues must match the intensity of the immune response to the severity of a biological threat. Toll-like receptors allow epithelial cells to identify microbe associated molecular patterns. However, the mechanisms that mitigate biological noise in single cells to ensure quantitatively appropriate responses remain unclear. Here we address this question using single cell and single molecule approaches in mammary epithelial cells and primary or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(35 citation statements)
references
References 63 publications
(82 reference statements)
1
34
0
Order By: Relevance
“…In addition to stochastic expression, epigenetic promoter regulation can create multigenerational cell states. For example, epigenetic regulation at one of the TLR promoters showed the predisposition of a subpopulation of human epithelial cells to respond to pathogen-associated molecular patterns (PAMPs) [92]. Lineage tracing coupled with modeling revealed that multiple gene modules, including those important for IFN-I signaling, were expressed only in small fractions of the total cell population, implying that the corresponding epigenetic signatures might predict which cells would become responders, and which ones would not [92].…”
Section: Trends In Immunologymentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to stochastic expression, epigenetic promoter regulation can create multigenerational cell states. For example, epigenetic regulation at one of the TLR promoters showed the predisposition of a subpopulation of human epithelial cells to respond to pathogen-associated molecular patterns (PAMPs) [92]. Lineage tracing coupled with modeling revealed that multiple gene modules, including those important for IFN-I signaling, were expressed only in small fractions of the total cell population, implying that the corresponding epigenetic signatures might predict which cells would become responders, and which ones would not [92].…”
Section: Trends In Immunologymentioning
confidence: 99%
“…For example, epigenetic regulation at one of the TLR promoters showed the predisposition of a subpopulation of human epithelial cells to respond to pathogen-associated molecular patterns (PAMPs) [92]. Lineage tracing coupled with modeling revealed that multiple gene modules, including those important for IFN-I signaling, were expressed only in small fractions of the total cell population, implying that the corresponding epigenetic signatures might predict which cells would become responders, and which ones would not [92]. Of note, the expression of these gene modules was transiently heritable, while studies in vitro showed that, in most cases, these modules were transcriptionally silenced after several generations, suggesting a complicated underlying mechanism of determining cell fate [92].…”
Section: Trends In Immunologymentioning
confidence: 99%
See 1 more Smart Citation
“…Beyond this regulation of intrinsic transcriptional noise, ERVs are also known to exhibit high epigenetic variability, 152,153 which may contribute to a higher order patterns of variability, such as the bimodal responsiveness of single cells to interferon signaling or differences across individuals. Like the lower order intrinsic noise that smooths signal responses through temporal variability, variability in interferon responsiveness is also thought to be functional, allowing for a flexible and tunable immune response 154 . The balance of the immune response between restraint and proper activity is crucial to organismal health and difficult to achieve through a global all‐or‐nothing signal.…”
Section: Why Are Viruses Repeatedly Co‐opted For Immunity?mentioning
confidence: 99%
“…Recent developments in experimental technology, such as single-cell RNA-seq (scRNA-seq) have made it feasible to study the transcriptomic profiles of individual cells, yielding new insights about cellular heterogeneity at the single-cell level [15]. Heterogeneity in cell populations is known to play a role in many biological contexts, including drug response in cancer [16]- [18], latency in HIV cells [19], [20], immune response in epithelial tissue [21], determination of cell fate in genetically identical populations [22]- [31], and "bet-hedging" responses to environmental stresses in bacteria [32], [33]. For more information, an excellent review of the study of cellular heterogeneity can be found in the Altschuler and Wu (2010) paper "Cellular Heterogeneity: When Do Differences Make a Difference?"…”
Section: Introductionmentioning
confidence: 99%